The potent activation of Ca2+-activated K+ current by NVP-AUY922 in the human pancreatic duct cell line (PANC-1) possibly independent of heat shock protein 90 inhibition - Nai-Jung Chiang; Sheng-Nan Wu; Li-Tzong Chen (Elsevier, 2015)
NVP-AUY922 (AUY) is a potent inhibitor of heat shock protein 90 (HSP90). Whether this compound can exert additional effects on membrane ion channels remains elusive. We investigated the effect of AUY on ion currents in human pancreatic duct epithelial cells (PDECs), including PANC-1 and MIA PaCa-2. AUY increased the amplitude of the K+ current (IK) in PANC-1 cells shown by whole-cell configuration. Single-channel recordings revealed a large-conductance Ca2+-activated K+ (BKCa) channel in PANC-1, but not in MIA PaCa-2. In cell-attached mode, AUY increased the probability of BKCa channel opening and also potentiated the activity of stretch-induced channels. However, other HSP inhibitors, 17-AAG or BIIB021 only slightly increased the activity of BKCa channels. In inside-out recordings, sodium hydrosulphide or caffeic acid phenethyl ester increased the activity of BKCa channels, but AUY did not. We further evaluated whether conductance of Ca2+-activated K+ channels (IK(Ca)) influenced secretion of HCO3− and fluid in PDECs by using a modified Whitcomb-Ermentrout model. Simulation studies showed that an increase in IK(Ca) resulted in additional secretion of HCO3− and fluid by mimicking the effect of AUY in PDECs. Collectively, AUY can interact with the BKCa channel to largely increase IK(Ca) in PDECs.